In-situ synthesis TiN enhanced high-entropy alloy cladding layer and preparation method
By in situ autogenerating the TiN phase in the high-entropy alloy cladding layer and improving the phase composition with Al elements, the problem of insufficient wear resistance of the high-entropy alloy cladding layer in harsh environments is solved, and significant hardness and wear resistance are improved.
Patent Information
- Application Number
- CN202510008929.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high entropy alloy cladding layers are difficult to meet the wear resistance requirements in harsh environments, especially under high temperature and high wear conditions.
The high-entropy alloy cladding layer preparation method is adopted to enhance in situ autogenerated TiN, and the in situ autogenerated TiN phase is used in the high-entropy alloy cladding layer through laser cladding technology, and the phase composition is improved and the TiN size is refined by combining Al elements.
The hardness, wear resistance and high-temperature oxidation resistance of the high-entropy alloy cladding layer are significantly improved, and the wear resistance is increased by about 6.31-19.77 times that of the DT4 matrix.
Smart Images

Figure CN119710681A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high entropy alloy cladding layers, and in particular to an in-situ self-generated TiN-enhanced laser-cladding high entropy alloy cladding layer and a preparation method thereof. Background Art
[0002] High entropy alloys are composed of five or more main elements in nearly equal molar ratios. Their high configurational entropy is conducive to the formation of simple solid solution phases rather than complex structural phases such as intermetallic compounds. Factors such as large atomic size differences, large lattice distortion, and slow diffusion make high entropy alloys exhibit high hardness, good corrosion resistance and wear resistance. They have been extensively studied in many fields such as structural materials, high hardness coatings, and energy storage materials, and are promising candidates for high-performance coating applications.
[0003] The performance of ceramic phase-enhanced coatings has been widely used in the industrial field. Ceramic particles form a dispersion-strengthened phase in the coating. These dispersion-strengthened phases can effectively prevent grain growth and slip, and can significantly improve the overall performance of the composite material. Transition metal nitrides have high hardness, oxidation stability and wear resistance, and are often used as protective materials to enable coatings to have better performance in friction and corrosion environments. TiN, (Ti, Al) N, (Al, Cr) N and similar nitride-based materials synthesized by chemical, physical or vapor deposition have been developed to protect various processed parts from wear and oxidation. In addition, research on nitride coatings for high entropy alloys mostly focuses on the mechanical properties and microstructure of high entropy alloy films. For example, FeCoNiCuVZrAl, TiZrHfNiCuCo, NbTiAlSiW were deposited by magnetron sputtering. x N y High entropy alloy multi-component nitride films, which have an amorphous structure and show extraordinary hardness. However, the thickness of magnetron sputtering films is only a few nanometers to a maximum of 5 microns, which cannot meet the service life of parts that resist wear in harsh environments.
[0004] Recently, more and more efforts have been made to develop high entropy alloy cladding layers to improve mechanical and high temperature properties. Laser cladding is one of the mature preparation technologies for surface modification of high entropy alloys. It has the advantages of high efficiency, high controllability, wide applicability, low dilution rate and small heat affected zone. Combining high entropy alloys with laser cladding technology can obtain high-performance cladding layers that are well metallurgically bonded to the substrate, thereby improving the comprehensive mechanical properties of the material surface.
[0005] The methods for obtaining ceramic reinforcement phase mainly include mechanical addition method and in-situ self-generation method. Direct doping of ceramic particles will lead to various types of defects, such as increasing the crack tendency of the cladding layer and the aggregation of ceramic particles. The in-situ self-generation method overcomes the problems of poor wettability and weak bonding between the ceramic reinforcement phase and the substrate in the addition method, and also reduces the possibility of defects such as pores and cracks in the cladding layer caused by the ceramic phase, which is conducive to obtaining a high-performance cladding layer with uniform and fine structure and uniform distribution of the reinforcement phase. Moreover, the deposition is completed while the ceramic reinforcement phase is generated, which is conducive to improving production efficiency and reducing production costs. Therefore, based on the strengthening mechanism of the high-entropy alloy cladding layer, the ceramic phase is used to in-situ self-generation to strengthen the high-entropy alloy cladding layer. It is found that ceramic particles can effectively inhibit the adhesion and wear of the material and improve its tribological properties in a stable state. In addition, during the laser cladding process, Ti atoms have a strong affinity with N atoms in the atmosphere, and TiN phase can be self-generated in situ in the cladding layer in the N2 atmosphere. At present, there is still a lack of in-depth research on the application of in-situ self-generated TiN ceramic phase reinforced high entropy alloys at home and abroad. By changing the content of transition metal elements in the high entropy alloy system, the mechanical properties of the cladding layer can be improved due to the influence of solid solution lattice distortion, second phase strengthening and even nanophase. From this perspective, the laser cladding technology was used to prepare the in-situ self-generated TiN high entropy alloy cladding layer. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing an in-situ self-generated TiN-reinforced high-entropy alloy cladding layer with good wear resistance, and to provide an in-situ self-generated TiN-reinforced high-entropy alloy cladding layer with good wear resistance.
[0007] In order to solve the above technical problems, a method for preparing an in-situ self-generated TiN-enhanced high-entropy alloy cladding layer comprises the following steps:
[0008] S1. Substrate pretreatment: Select iron plate as the substrate and grind its surface to remove oxide scale;
[0009] S2. Powder pretreatment: select Al, Co, Cr, Ni and Ti spherical powders with a particle size of 45-105 μm as cladding powders, the molar ratio of Al, Co, Cr, Ni and Ti spherical powders is x:1:1:1:1, 0<x≤1, and mix all powders evenly;
[0010] S3. For laser cladding, industrial nitrogen is used as both the protective gas and the powder feeding gas.
[0011] Preferably, the iron plate is DT4 pure iron plate.
[0012] Preferably, in step S2: x=0.5.
[0013] Preferably, in step S2: x=1.
[0014] Preferably, in step S3, the purity of the industrial nitrogen is greater than or equal to 99.9%.
[0015] Preferably, in step S3: coaxial powder feeding is used for laser cladding, the powder feeding speed is 8 g / min, the flow rate of shielding gas is 15 L / min, and the flow rate of powder feeding gas is 6 L / min; the laser cladding parameters are: laser power 1000 W, scanning speed 12 mm / s, spot diameter 2 mm, overlap rate 30%.
[0016] Preferably, in step S1, the surface of the substrate is polished using 80# SiC sandpaper, the polished substrate is ultrasonically cleaned for 20 minutes, and then placed in a vacuum drying oven and dried at 200° C. for 2 hours.
[0017] Preferably, in step S2, the purity of each powder used is higher than 99.9%, and the powders are uniformly mixed for 2 hours using a V-type powder mixer. The uniformly mixed powders are dried in a vacuum drying oven at 120° C. for 2 hours.
[0018] The in-situ self-generated TiN-enhanced high-entropy alloy cladding layer of the present invention is prepared by any of the above-mentioned methods for preparing an in-situ self-generated TiN-enhanced high-entropy alloy cladding layer.
[0019] The beneficial effects of the present invention are as follows: the present invention adopts special alloy powder and special laser cladding conditions, can self-generate TiN in situ, improve the performance of the high entropy alloy cladding layer by self-generating TiN in situ, selects industrial nitrogen as the protective gas and the powder feeding gas, can ensure the full reaction between the alloy element and the N element, is conducive to the generation and uniform distribution of TiN, and the spherical powder particle size of the selected element is 45-105μm in order to improve the powder fluidity and obtain a high entropy alloy cladding layer with good forming and uniform performance.
[0020] The present invention realizes a good combination of in-situ self-generated TiN and high-entropy alloy, and effectively improves the hardness, wear resistance and high-temperature oxidation resistance of the high-entropy alloy cladding layer and the DT4 pure iron substrate.
[0021] The present invention adds Al element to improve the phase composition of the cladding layer, which can refine the size of TiN and greatly improve its wear resistance.
[0022] The preparation process of the present invention is simple and easy to implement, which promotes the wide application of high entropy alloys in material surface engineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The comparative example 1CoCrFeNiTi and the examples 1 to 4Al xXRD diffraction patterns of CoCrFeNiTi (x=0.25; 0.5; 0.75 and 1) high entropy alloy cladding layers.
[0024] Figure 2-1 This is a microstructure diagram of the CoCrFeNiTi high entropy alloy cladding layer of comparative example 1 of the present invention.
[0025] Figure 2-2 Example 1A1 0.25 Microstructure of CoCrFeNiTi high entropy alloy cladding layer.
[0026] Figure 2-3 Example 2A1 0.5 Microstructure of CoCrFeNiTi high entropy alloy cladding layer.
[0027] Figure 2-4 Example 3A1 0.75 Microstructure of CoCrFeNiTi high entropy alloy cladding layer.
[0028] Figure 2-5 This is the microstructure diagram of the AlCoCrFeNiTi high entropy alloy cladding layer of Example 4.
[0029] Figure 2-6 Example 3A1 of the present invention 0.5 Point scanning diagram corresponding to TiN in the CoCrFeNiTi high entropy alloy cladding layer.
[0030] Figure 3-1 The comparative example 1CoCrFeNiTi and the examples 1 to 4Al x Microhardness distribution of CoCrFeNiTi (x=0.25; 0.5; 0.75 and 1) high entropy alloy cladding layer.
[0031] Figure 3-2 The comparative example 1CoCrFeNiTi and the examples 1 to 4Al x Average microhardness diagram of CoCrFeNiTi (x=0.25; 0.5; 0.75 and 1) high entropy alloy cladding layers.
[0032] Figure 4-1 The comparative example 1CoCrFeNiTi and the examples 1 to 4Al x Depth and width of wear marks of CoCrFeNiTi (x=0.25; 0.5; 0.75 and 1) high entropy alloy cladding layer and DT4 pure iron.
[0033] Figure 4-2 The comparative example 1CoCrFeNiTi and the examples 1 to 4Al xWear rates of CoCrFeNiTi (x = 0.25; 0.5; 0.75 and 1) high entropy alloy cladding layers and DT4 pure iron.
[0034] Figure 5 Comparative Example 1CoCrFeNiTi of the present invention, Examples 1 to 4Al x Oxidation weight gain curves of CoCrFeNiTi (x=0.25; 0.5; 0.75 and 1) high entropy alloy cladding layer and DT4 pure iron. DETAILED DESCRIPTION
[0035] The instruments, reagents, materials, etc. involved in the following comparative examples and embodiments, unless otherwise specified, are conventional instruments, reagents, materials, etc. already available in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following embodiments, unless otherwise specified, are conventional experimental methods, detection methods, etc. already available in the prior art.
[0036] This specific comparative example and embodiment prepares an in-situ self-generated TiN-enhanced high entropy alloy cladding layer according to the following method:
[0037] The DT4 pure iron plate substrate was polished to remove the oxide scale, and the substrate surface was polished with 80# SiC sandpaper. The polished substrate was ultrasonically cleaned for 20 minutes, and then placed in a drying oven at 200°C for 2 hours. Other methods can also be used as long as the oxide scale on the substrate surface can be removed and dried.
[0038] Spherical Al, Co, Cr, Ni and Ti powders are dried in a vacuum drying furnace at 120°C for 2 hours, and then uniformly mixed according to the molar ratio of x:1:1:1:1 (x=0; 0.25; 0.5; 0.75 and 1), and the purity of each powder is higher than 99.9%. The powders are uniformly mixed for 2 hours using a V-type powder mixer. The particle size of the spherical powder is 45-105μm. Each value of x represents an example, and the examples are the same only in terms of the value of x. x=0 is comparative example 1; x=0.25 is example 1; x=0.5 is example 2; x=0.75 is example 3, and x=1 is example 4.
[0039] Laser cladding method: coaxial powder feeding is used for laser cladding, industrial nitrogen is used as both shielding gas and powder feeding gas, and the purity of industrial nitrogen is greater than or equal to 99.9%. The cladding is performed under the conditions of laser power of 1000W, scanning speed of 12mm / s, spot diameter of 2mm, overlap rate of 30%, shielding gas flow of 15L / min, powder feeding gas of 6L / min, and powder feeding speed of 8g / min, to obtain an in-situ self-generated TiN-enhanced high entropy alloy cladding layer, that is, comparative example 1CoCrFeNiTi and examples 1 to 4Al xCoCrFeNiTi (x=0.25; 0.5; 0.75 and 1) high entropy alloy cladding layer.
[0040] Figure 1 CoCrFeNiTi, Al 0.25 CoCrFeNiTi、Al 0.5 CoCrFeNiTi、Al 0.75 From the XRD diffraction patterns of CoCrFeNiTi and AlCoCrFeNiTi high entropy alloy cladding layers, it can be seen that with the addition of Al, the phase evolution process of each cladding layer is: FCC phase + Laves phase + TiN → BCC / B2 phase + L12 phase + Laves phase + TiN → BCC / B2 phase + TiN.
[0041] Formation mechanism of TiN: Ti is a strong nitride-forming element, and the mixing enthalpy of Ti and N is -190 kJ / mol, which can react with N to form stable nitrides. Therefore, during the laser cladding process, under the condition of sufficient N source, Ti can react with N to form TiN.
[0042] Figure 2-1 , Figure 2-2 , Figure 2-3 , Figure 2-4 , Figure 2-5 CoCrFeNiTi, Al 0.25 CoCrFeNiTi、Al 0.5 CoCrFeNiTi、Al 0.75 The microstructure of CoCrFeNiTi and AlCoCrFeNiTi high entropy alloy cladding layers and the corresponding point scanning diagram of TiN show that the Ti element fully reacts with N2 to generate an in-situ self-generated TiN strengthening phase that is evenly dispersed in the cladding layer. With the increase of Al content, the size of TiN is significantly refined. The TiN size of the AlCoCrFeNiTi cladding layer is the finest, accounting for 47.4%-74.5% of that of other cladding layers.
[0043] Figure 3-1 and Figure 3-2 CoCrFeNiTi, Al 0.25 CoCrFeNiTi、Al 0.5 CoCrFeNiTi、Al 0.75 Microhardness distribution and average microhardness of CoCrFeNiTi and AlCoCrFeNiTi high entropy alloy cladding layers. It can be seen that CoCrFeNiTi, Al 0.25 CoCrFeNiTi、Al 0.5 CoCrFeNiTi、Al 0.75The average microhardness of CoCrFeNiTi and AlCoCrFeNiTi high entropy alloy cladding layers are 911.81, 950.78, 1000.50, 873.80, and 815.91 HV, respectively, which are significantly higher than the DT4 matrix (about 150 HV), and are about 5.44-6.67 times that of the matrix. With the addition of Al, the solid solution strengthening effect is enhanced, causing the lattice distortion effect, promoting the formation of BCC / B2 phase and nanophase L12, and promoting the transformation of the matrix phase from dendrite to equiaxed crystal. At the same time, the size of the in-situ self-generated TiN gradually decreases, and the size uniformity increases.
[0044] Figure 4-1 and Figure 4-2 CoCrFeNiTi, Al 0.25 CoCrFeNiTi、Al 0.5 CoCrFeNiTi、Al 0.75 The wear depth, width and wear rate of CoCrFeNiTi, AlCoCrFeNiTi high entropy alloy cladding layers and DT4 pure iron. The wear depth, width and wear rate of each high entropy alloy cladding layer are significantly lower than that of DT4 substrate, indicating that the wear resistance of each high entropy alloy cladding layer is significantly better than that of DT4 substrate. 0.25 CoCrFeNiTi、Al 0.5 CoCrFeNiTi、Al 0.75 The wear rates of CoCrFeNiTi and AlCoCrFeNiTi cladding layers are 25.05×10 -6 , 19.98×10 -6 ,7.99×10 -6 , 12.25×10 -6 and 14.39×10 -6 mm 3 / (N·m), the wear rate of DT4 substrate is 1.58×10 -4 mm 3 / (N·m), the wear resistance of each cladding layer is about 6.31-19.77 times that of the DT4 substrate. 0.5 The wear rate of CoCrFeNiTi is the smallest and its wear resistance is the strongest. Its wear resistance is about the same as CoCrFeNiTi and Al 0.25 CoCrFeNiTi、Al 0.5 CoCrFeNiTi、Al 0.75 1.53-3.14 times of CoCrFeNiTi cladding layer. 0.5The reasons why the CoCrFeNiTi cladding layer has the strongest wear resistance are: first, TiN and Laves phase participate in the wear process as reinforcing phases, which increases the resistance to plastic deformation and plowing of the cladding layer. Secondly, the solid solution of Al element causes the matrix phase of the cladding layer to transform from FCC phase to BCC / B2 phase. Compared with FCC phase, BCC / B2 phase has higher hardness, which plays a positive role in improving wear resistance. In addition, BCC / B2 phase effectively connects Laves phase with TiN phase, which improves the toughness of HEA cladding layer. Thirdly, the coherent interface between TiN phase and Laves phase can maintain a stable phase boundary. The lower free energy and higher interface strength of the coherent interface will enhance the bonding strength between TiN and high entropy alloy cladding layer, thereby ensuring that TiN phase is not easy to fall off during friction, and TiN phase plays a "pinning" role on the grain boundary, inhibiting grain boundary migration and growth, thereby refining the microstructure of HEA cladding layer. In addition, TiN acts as a heterogeneous nucleation point during the crystallization of the molten pool, which increases the nucleation rate and plays a role in grain refinement. Fourth, with the addition of Al elements, the size of TiN in the HEA cladding layer gradually decreases and the uniformity increases. The in-situ formed ceramic phase particles play a role in second phase strengthening and dislocation strengthening. Therefore, Al 0.5 The CoCrFeNiTi high entropy alloy cladding layer has the best wear resistance.
[0045] Figure 5 CoCrFeNiTi, Al 0.25 CoCrFeNiTi、Al 0.5 CoCrFeNiTi、Al 0.75 Weight gain curves of CoCrFeNiTi, AlCoCrFeNiTi high entropy alloy cladding layer and DT4 substrate after high temperature oxidation for 100h. It can be seen that the mass gain of the high entropy alloy cladding layer increases parabolically with time. 0.25 CoCrFeNiTi、Al 0.5 CoCrFeNiTi、Al 0.75 The mass gains of CoCrFeNiTi and AlCoCrFeNiTi cladding layers after oxidation for 100 h are 24.39, 18.89, 14.06, 6.89 and 6.06 mg / cm -2 The mass gain of DT4 matrix increases linearly with time. After 100h of oxidation, its mass gain is 207.43mg / cm -2. The high-temperature oxidation resistance of each cladding layer is about 8.50-34.23 times that of the DT4 substrate. Among them, the AlCoCrFeNiTi high-entropy alloy cladding layer has the lowest mass gain after 100h of high-temperature oxidation and the strongest high-temperature oxidation resistance, which is about 1.14-4.02 times that of other cladding layers. The reason why the AlCoCrFeNiTi cladding layer has the strongest resistance to high-temperature oxidation: With the addition of Al content, a continuous and dense Al2O3 layer is formed on the surface of the cladding layer, which prevents the internal diffusion of O2 and the external diffusion of other metal elements, thereby improving the oxidation resistance of the cladding layer.
[0046] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an in-situ self-generated TiN-enhanced high-entropy alloy cladding layer, characterized in that: The following steps are involved: S1. Substrate pretreatment: Select iron plate as the substrate and grind its surface to remove oxide scale; S2. Powder pretreatment: select Al, Co, Cr, Ni and Ti spherical powders with a particle size of 45-105 μm as cladding powders, the molar ratio of Al, Co, Cr, Ni and Ti spherical powders is x:1:1:1:1, 0<x≤1, and mix all powders evenly; S3. For laser cladding, industrial nitrogen is used as both the protective gas and the powder feeding gas.
2. The method for preparing an in-situ self-generated TiN-enhanced high-entropy alloy cladding layer according to claim 1, characterized in that: The iron plate is DT4 pure iron plate.
3. The method for preparing an in-situ self-generated TiN-enhanced high-entropy alloy cladding layer according to claim 1, characterized in that: In step S2: x=0.
5.
4. The method for preparing an in-situ self-generated TiN-enhanced high-entropy alloy cladding layer according to claim 1, characterized in that: In step S2: x=1.
5. The method for preparing an in-situ self-generated TiN-enhanced high-entropy alloy cladding layer according to claim 1, characterized in that: In step S3, the purity of the industrial nitrogen is greater than or equal to 99.9%.
6. The method for preparing an in-situ self-generated TiN-enhanced high-entropy alloy cladding layer according to claim 1, characterized in that: In step S3: coaxial powder feeding is used for laser cladding, the powder feeding speed is 8g / min, the flow rate of shielding gas is 15L / min, and the flow rate of powder feeding gas is 6L / min; the laser cladding parameters are: laser power 1000W, scanning speed 12mm / s, spot diameter 2mm, overlap rate 30%.
7. The method for preparing an in-situ self-generated TiN-enhanced high-entropy alloy cladding layer according to claim 1, characterized in that: In step S1, the surface of the substrate is polished using 80# SiC sandpaper, the polished substrate is ultrasonically cleaned for 20 minutes, and then placed in a vacuum drying oven and dried at 200° C. for 2 hours.
8. The method for preparing an in-situ self-generated TiN-enhanced high-entropy alloy cladding layer according to claim 1, characterized in that: In step S2, the purity of each powder used is higher than 99.9%, and the powders are uniformly mixed for 2 hours using a V-type powder mixer. The uniformly mixed powders are dried in a vacuum drying oven at 120° C. for 2 hours.
9. An in-situ self-generated TiN-enhanced high entropy alloy cladding layer, characterized in that: The invention is prepared by adopting the method for preparing an in-situ self-generated TiN-reinforced high entropy alloy cladding layer as claimed in any one of claims 1 to 8.